CFD simulations and experimental measurements of flow past free-surface piercing, finite length cylinders with varying aspect ratios. (10th September 2016) - Benitz, M.A.; Carlson, D.W.; Seyed-Aghazadeh, B.; Modarres-Sadeghi, Y.; Lackner, M.A.; Schmidt, D.P.
Highlights: We simulate (with CFD) and experimentally measure loads on surface-piercing cylinders with free-ends of varying aspect ratios. A wider range of aspect ratios than has previously been investigated is covered. Drag coefficients and the presence of vortex shedding diminish greatly with decreasing aspect ratio. Furthermore, loads along the length of a cylinder are investigated. The free-surface and free-end affect the load behavior, with ramifications to offshore structural engineering. Abstract: In this work, the flow past surface-piercing cylinders with free lower ends is studied numerically with computational fluid dynamics (CFD) at varying aspect ratios (AR = H/D) from around 1 to 19, and compared against experimental measurement across the same range. Numerical and experimental work is carried out at Re = 2900 and Fr = 0.65. The aspect ratio of the cylinder is varied by raising and lowering the cylinder into the water. The resulting flow field and loads on the cylinder as a result of changing the cylinder's depth of submergence are investigated in terms of drag, lift and frequency content. First, the effects of changing the aspect ratio are examined. CFD simulations demonstrate a reduced drag coefficient, consistent with the experimental measurements, as compared to a fully-submerged, infinite cylinder at the same Reynolds number. A significant reduction in the drag coefficient is observed at an aspect ratio of 2. For aspect ratios 3 and below, Karman vortex shedding is completely suppressed due to the dominance of free surface effects. With increasing aspect ratio the Strouhal number is found to approach 0.2. Second, the flow regime is investigated as a function of cylinder length for a cylinder with aspect ratio of 12. Different regions of vortex shedding are observed along the length of the cylinder, as demonstrated by lift forces, Strouhal numbers and CFD flow visualizations. Strouhal numbers below 0.2 were observed for regions near the free surface. Additionally, the drag coefficient was found to decrease near the free surface. This study over a wide range of aspect ratios exhibits the effects of a free surface, free end and also the length of the cylinder on both the flow regime and loading.